Parental awareness and knowledge for participating in talent selection of golf - AGOPYAN, ANİ; ÇOTUK, MÜFİDE; GÜLER, MELİKE LALE (My University, 2017)
The aim of this study was to determine the golf knowledge and awareness of the parents whose children were involved in a golf talent selection project. It was held in order to spread golf and find new talents in Turkey. A questionnaire was applied to the parents of 400 children (223 boys and 178 girls) aged 8-11 during this project. Frequency distribution was used for each question (p<0.05). As a result, the majority of the parents who live in Silivri - where one of the well-known golf facilities in Turkey is located - did not have any knowledge about golf but the majority of the parents (97.3%) wanted their children to be involved in golf. This was not effective to bring their children for the project because more than half of the parents brought their children for golf talent selection leading by their of physical education and sport teachers (53.6 %). In addition more than half of the parents were active in sports therefore they encouraged and supported their children to play golf
Keywords: parental awareness; golf; role modelling; children; talent selection